'The development of physical education in Northern Ireland, 1922-1953 and the role of Joan Burnett Knight'. Issue 8 (2nd August 2020) - Curran, Conor
ABSTRACT: This article examines the state of Physical Education in Northern Ireland's schools before, during and after the Second World War with a focus on government changes and the role of one of the first organisers to be appointed there to cater for the subject. In the mid-1920s, the new Northern Ireland Ministry of Education was initially of the view that the teaching of physical education was being adequately catered for. However, a scarcity of facilities in many schools and the poor levels of staff expertise in the subject meant that standards remained low in comparison with other nations in Western Europe, despite the area being part of the United Kingdom. Following the passing of the 1938 Physical Training and Recreation Bill, the appointment of inspectors and organisers for physical education by the Northern Ireland Ministry of Education was an important step in improving the situation. Despite this, the provision of trained PE teachers remained an issue throughout the 1940s and following much discussion, in 1953, the first PE College for female students in Northern Ireland was established. Within this context, this paper explores the early career of Joan Burnett Knight, an English-born PE organiser who was employed there from 1944-1950. Through her work in the schools, and her organisation of short-term training course for teachers, along with her public activities, she was able to raise awareness of the value of the subject. This article also discusses the 1949 Lingiad Games, in which she led the Northern Ireland team. In doing so, it illustrates Miss Burnett Knight's career aspirations and her independent character before the establishment of gender equality measures in employment and at a time when many women were confined to domestic roles.